Thermal characteristic investigation of eutectic composite fatty acid as heat storage material for solar heating and cooling application - Thaib R.; Fauzi H.; Ong H.C.; Rizal S.; Mahlia T.M.I.; Riza M. (Institute of Physics Publishing, 2023)
Conductive materials; Differential scanning calorimetry; Dye-sensitized solar cells; Eutectics; Heat storage; Mixtures; Phase change materials; Purification; Saturated fatty acids; Thermoanalysis; Thermodynamic stability; Absorbance spectrum; Chemical compatibility; Composite phase change materials; Fatty acid eutectics; Fourier transform infra reds; Physical and chemical properties; Solar heating and cooling; Thermal characteristics; Thermal conductivity